Detection of nimesulide metabolites in rat plasma and hepatic subcellular fractions by HPLC-UV/DAD and LC-MS/MS studies - (:unkn) unknown (Editions Medecine et Hygiene, 2005)
Nimesulide (4-nitro-2-phenoxymethanesulfonanilide) is an atypical NSAID lacking a carboxylic acid moiety. It has a good gastric tolerability due to selective inhibition of COX-2. The study objectives in the present work were to characterize the metabolism of nimesulide in rat plasma at certain time intervals. In vitro studies were also carried out to examine if nitroreduction takes place in vitro using rat hepatic subcellular fractions (microsomal and S9 fraction) besides aromatic hydroxylation. This communication describes detection and characterization of nimesulide metabolites isolated from plasma and hepatic subcellular post-incubates by the use of HPLC-UV/diode array and LC-MS/MS. Hydroxynimesulide was the major metabolite both in vivo and in vitro whereas nitroreduction was observed only in vitro with subcellular fractions under anaerobic conditions.
Keywords: LC-MS/MS; Nimesulide; Nitroarenes; Nitroreduction; S9 fraction